Pharmaco-utilization of biologic drugs in patients affected by psoriasis, psoriatic arthritis and ankylosing spondylitis in an Italian real-world setting. (2nd September 2020) - Zagni, Emanuela; Colombo, Delia; Fiocchi, Martina; Perrone, Valentina; Sangiorgi, Diego; Andretta, Margherita; De Sarro, Giovambattista; Nava, Eduardo; Degli Esposti, Luca
ABSTRACT: Background: As primary aim the study evaluated the monthly average dose for biologic drugs used for psoriasis (PSO), psoriatic arthritis (PsA) and ankylosing spondylitis (AS) in real-world settings. Methods: This retrospective analysis was based on administrative databases of Italian Entities. Adult patients diagnosed PSO, PsA or AS with ≥1 prescription of biologic drugs indicated for these diseases were included during 01/01/2011 – 30/06/2017. Monthly average dose and persistence were evaluated during 6-months after inclusion (follow-up). Results: Overall, 6, 179 patients prescribed biologic drugs were included: 2, 373 represented the 1.1% of PSO-patients, 2, 756 the 37.4% of PsA-patients, 1, 050 the 17.8% of AS-patients. Monthly average dose was: 69 mg (PSO), 73 mg (PsA), 70 mg (AS) for adalimumab; 152 mg (PSO), 155 mg (PsA), 147 mg (AS) for etanercept; 140 mg (PSO), 133 mg (PsA), 166 mg (AS) for infliximab; 255 mg (PSO), 183 mg (PsA), 154 mg (AS) for secukinumab. Persistance to adalimumab was 76%(PSO), 78%(PsA), 74%(AS); with etanercept 77% in each disease-cohort; with infliximab 67%(PSO), 71%(PsA), 88%(AS); with secukinumab 91%(PSO) and 85%(PsA). Conclusion: The study described real-world dosing patterns of biologics indicated for PSO, PsA, or AS, suggesting a trend of monthly average dose generally lower than the dosage indicated in the datasheet.